Does the Constitutional Court on Local Election Responsive Decisions ? - Al-Fatih, Sholahuddin; Nur, Asrul Ibrahim (Lembaga Contrarius Indonesia, 2023)
The dynamism of the implementation of general elections in Indonesia is directly related to the legal products that regulate them. In this case, legal politics that continue to change legal products can further complicate the systems, mechanisms, and behavior of general election organizers and participants, and make them vulnerable to future general election disputes. This article aims to explain how the legal politics of the Constitutional Court's decision regarding the Regional General Election Law influences changes to the Regional Head Election Law, as well as its responsiveness to regional head general elections. This article uses a normative legal research method with a statute approach which focuses on the analysis of Constitutional Court decisions regarding regional head elections. In addition, the author presents a comparison of the legal politics of general election regulation in Indonesia and in the USA and Europe. This article finds that the Constitutional Court's authority to adjudicate regional elections has become permanent after almost a decade and a half of legal uncertainty and doubt. During that time, legal politics in several Constitutional Court decisions regarding regional head election cases had a similar character, namely producing responsive legal products. This indicates that democracy in Indonesia is built based on fulfilling human dignity, fairness, and justice. Thus, the issue of regional head general elections could have its origins in other things but not in the legal politics of the Constitutional Court's decision and its influence on related laws.